A text-book of ore and stone mining - Foster, Clement le Neve, 1841-1904 (Charles Griffin, 1894)
This 19th century textbook illuminates the art of mining. Foster explains the principles of the art, solves difficulties which perplex the beginner, suggests matters which he should observe and supplies a system for arranging ideas methodically.